The description of dendriform algebra structures on two-dimensional complex space - M. Rikhsiboev, Ikrom; Sattarovich, Rakhimov Isamiddin; Basri, Witriany (Scientific Advances Publisher, 2010)
In this paper, we classify all dendriform algebra structures on two-dimensional complex space. We distinguish twelve isomorphism classes (one parametric family and eleven concrete) of two-dimensional complex dendriform algebras, and show that they exhaust all possible cases.